(untitled) (Journal of Global Humanities and Social Sciences, 2025)
This paper conducts an in-depth exploration of the application of virtual reality (VR) technology in the training of Master of Tourism Administration (MTA) students. It analyzes the demand for innovative talents in the tourism industry in the digital era, emphasizing the important value of VR in expanding tourism education theories, promoting interdisciplinary research, exploring new learning models, and addressing the bottlenecks of traditional training approaches. Based on the analysis of the current application status of VR technology in tourism management education both domestically and internationally, the paper discusses the shortcomings of J College in terms of curriculum system, teaching faculty, and practical teaching. It proposes several application strategies including strengthening faculty development, optimizing curriculum design, improving the practical teaching system, developing VR-based teaching materials, and leveraging the technical potential while tracking teaching outcomes. The aim is to assist J College and other institutions in innovating their MTA training models through VR, cultivating high-quality talents for the tourism industry, and promoting the synergy between tourism education and industry development.